Synthesis, Characterization of Nanocrystalline LaMnO3+δ and Its Application for the Removal of Chemical Oxygen Demand from Industrial Effluents - Nagaraja, R.; Nagappa, B.; Girija, C.R.; Nagabhushana, B.M.; Donappa, N.; Manjunatha Sastry, K. (Asian Journal of Chemistry, 2011)
Nanocrystalline LaMnO3+δ has been synthesized by low temperature initiated, self propagating solution combustion process. It is an inexpensive synthesis and readily yields nanocrystalline product. It was characterized by powder XRD, FT-IR and SEM. The surface area of product is ca. 24 m2/g. The SEM micrographs show that the product is voluminous, fluffy and porous. It is found that 60 mg of LaMnO3+δ powder could remove 85 % of chemical oxygen demand from 100 mL of industrial effluent at pH 10.